2016
DOI: 10.21037/jtd.2016.11.106
|View full text |Cite
|
Sign up to set email alerts
|

Lobectomy and limited resection in small-sized peripheral non-small cell lung cancer

Abstract: Background: Although lobectomy is the standard surgical procedure for non-small cell lung cancer (NSCLC), recent studies show favorable outcomes after limited resection in patients with small-sized peripheral tumors. We conducted a randomized controlled trial of such patients to estimate postoperative outcomes and pulmonary function following these surgical techniques.Methods: Between 2005 and 2008, eligible patients with tumors of 2 cm or less were randomly assigned 1:1 to undergo lobectomy or limited resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…This data may reflect the higher malignant potential of sADC, i.e., ADC with micropapillary pattern which is a well-known malignant factor (29,30). Previous studies demonstrated that sublobar resection was a potentially valid surgical option for small-sized tumors (3,4), while the results of large-scale multi-institutional prospective randomized trials are awaited to confirm this (e.g., JCOG0802 and CALGB140503). Furthermore, ADCs with a high proportion of ground glass opacity are classified as minimally invasive or non-invasive ADC (ADC in situ) (31), and complete resection of such minimally invasive or non-invasive ADCs leads to an extremely favorable prognosis (32,33).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This data may reflect the higher malignant potential of sADC, i.e., ADC with micropapillary pattern which is a well-known malignant factor (29,30). Previous studies demonstrated that sublobar resection was a potentially valid surgical option for small-sized tumors (3,4), while the results of large-scale multi-institutional prospective randomized trials are awaited to confirm this (e.g., JCOG0802 and CALGB140503). Furthermore, ADCs with a high proportion of ground glass opacity are classified as minimally invasive or non-invasive ADC (ADC in situ) (31), and complete resection of such minimally invasive or non-invasive ADCs leads to an extremely favorable prognosis (32,33).…”
Section: Discussionmentioning
confidence: 88%
“…Prior studies that analyzed the relationship between tumor size and prognosis revealed a favorable prognosis for small-sized tumors, especially those ≤2 cm in diameter (1,2). Both randomized and non-randomized studies have revealed good outcomes for patients who underwent sublobar resection of these small-sized tumors (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a future prospect, we believe that our findings can be applied to determine the indication for limited resection and aid surgical decision-making for primary lesions in other lung lobes. In recent years, limited resection is increasingly employed for patients with comorbid conditions, elderly patients, those with poor respiratory function or in patients with early-stage non-small cell lung cancer (17)(18)(19). Limited resection, especially wedge resection, is a less invasive alternative to lobectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Nishio et al have reported an association between the C/T on preoperative CT or the segment locations and postoperative locoregional control and/or outcomes in patients with NSCLC of ≤2 cm who underwent intentional extended segmentectomy. Many previous studies have suggested risk factors for postoperative locoregional recurrence and/or poor outcomes after limited resection, such as male sex, severe smoking history, high C/T on preoperative CT, high maximum standardized uptake values on F-18-fluorodeoxyglucose positron emission tomography/ CT, tumor histology other than adenocarcinoma, visceral pleural invasion, and lymphatic permeation (15,18,(20)(21)(22)(23). Limited resection for small-sized NSCLC patients with these risk factors is still controversial.…”
Section: Editorialmentioning
confidence: 99%